Integrated detectors of ionizing radiation based on ZnSe(Te)/pZnTe-nCdSe structures - Starzhinskiy, N.G.; Grinyov, B.V.; Gashin, P.A.; Focsha, A.A.; Galat, A.B.; Ryzhikov, V.D.; Katrunov, K.A.; Zenya, I.M. (Functional Materials, 2008)
A new type of solid state integrated detector of ionizing radiation has been proposed. It has been shown that the properties of ZnSe(Te) crystals make it possible to develop integrated detectors with photoreceivers of a photosensitive heterostructure type arranged directly on the scintillator surface. A preparation method of ZnSe(Te)/pZnTe—nCdSe detectors has been described and the output characteristics thereof have been obtained.